Potencial de captura de carbono en el cultivo de Piñón blanco (Jatropha curcas L.), en la estación experimental el Porvenir - Pinedo Rodríguez, Gunther (2011)
The present study of investigation was realized on the El Porvenir Experimental Station INIA-Tarapoto, Juan Guerra disctric, San martín province, San Martín deparment. It had as principal aim: To determine the potential of capture of Carbon in the cultivation on "Pifión Blanco" (Jatropha curcas L.), on the El Porvenir Experimental Station, and specific objects: a. Determine the amount of carbon contained in plants of "Pifión Blanco" (Jatropha e ureas L.). h. To determine the quantity of carbon contained in the soil. c. Develop an allometric relationship equation to calculate the amount of carbon captured in "Pifión Blanco" (Jatropha curcas L.) The factors of study were constituted by two treatments: T(A) dry season and T (B) wet season, which consisted of 5 repetitions for ages (1, 2, 3 and 4 years) and by epochs; for which we used 20 plants in dry season and 20 plants in wet season, it was estimated the biomass of shrub, and herbaceous stubble; also it was made an analysis of soil in the plots where is located the plantations of "Pifión Blanco" (Jatropha curcas L.). The experimental design was used experimental blocks at random, with 5 replicates, eaming a total of 20 repetitions per time, during the period of the months of January and April2011, considering the dry season (summer) and in the months of May and August 2011 considered wet season (winter). There were the collection of data for the determination of biomass in the plantations of "Pinon white", they extracted of soil samples to the corresponding physical-chemical analysis. A1l of these samples were taken to the laboratory specialized from the National Institute of Agricultura! Innovation - Tarapoto. This had as aim to verify the effectiveness of field results: l. Biomass is the sum total of the organic matter that is found in an ecosystem of a given time and is expressed in terms of dry weight, the biomass in the plantations of 1 year was greater in the dry season (0.88 kg.) that in the wet season (0.87 kg. ); In the plantations of 2 years biomass was higher in the dry season (5.77 kg.) that in wet season (5.53 kg.); in the plantations of 3 years biomass was higher in the dry season (8.98 kg.) that in the wet season (8.74 kg.) and biomass in plantations of 4 years was greater in the dry season (12.82 kg.) that in the wet season (12.49 kg.) respectively. The average total Moisture content in the aerial biomass in dry season for ages was; 305.97 % in plantations of 01 year, 284.19 % in plantations of 02 years, 278.38 % in plantations of 03 years and 286.07 % in plantations in 04 years. The total average number of moisture content in the aboveground biomass in wet season by age was; 313.44 % in plantations of 01 year, 290.87 % in plantations of02 years, 291.46% in plantations of03 years and 295.60% in plantations in 04 years. lt was noted that the percentage of moisture content is higher in wet season. The average percentage of ash in the stem was 1.68 % in the dry season and 1.34 % in wet season, in the branches was 1.25 % in the dry season and 1.11 % in wet season, in the leaves with 2.3 % in the dry season and 2.01 %in wet season, reaching a higher percentage in the leaves with a 2.52 % in the dry season and 2.14 % in wet season. 2. The average of total biomass, carbon content of co2 capture and in kilograms in the dry season of the "Pinon White" (Jatropha curcas L.), for plánts 1 year was 0.86 kg., 0,382 kg., and 1.399kg.; in plants, 2 years from 5.68 kg., 2,558 kg., and 9,379 kg.; in plants of 3 years of 8,86 kg., 3,868 kg., and 14,183 kg.; in plants of 4 years of 12.71 kg., 5,721 kg., and 20,977 kg respectively. 3. The average of total biomass, carbon content of co2 capture and in kilograms in the wet season of the "Pinon White" (Jatropha curcas L.), for plants of 1 year was 0.85 kg., 0,389 kg., and 1,426 kg.; in plants, 2 years of 5.46 kg., 2,455 kg., and 9,001 kg.; in plants of 3 years of 8.60 kg., 3,988 kg., and 14,624 kg.; in plants of 4 years from 12.32 kg., 5,546 kg., and 20,336 kg., respectively. 4. There was no statistical significance between the treatments by componenis and by ages assessed in the analysis of variance. 5. The equation generated: B = Jo-"·88456+l.3l6J6•Jog(d3J, type logarithmic. Key words: experimental blocks, equation generated.